AUV Thrust Allocation with Variable Constraints (Advances in Systems Science and Applications, 2017)
Modern multipurpose Autonomous Underwater Vehicles (AUVs) represent the nextgeneration of robotic systems with new technological tasks faced by researchers. One methodof extending the functionality of the vehicle is installing tunnel thrusters in addition to the sternpropulsion system. Thereby the vehicle becomes able to undertake both survey-style missionsand low speed interactions with the environment. But the efficiency of the tunnel thruster dependsstrongly on the vehicle’s velocity, due to hydrodynamic aspects. The usual solution to this problemuses different control models and thrust allocation methods for these types of mission. A unifiedapproach to thrust allocation is presented in this paper. The approach is based on solving theallocation problem by quadratic programming with variable constraints, depending on the velocityof the AUV and the thrusters’ angle of attack. The well-known implementation of active setmethod was used to model the proposed allocation method.